2001
DOI: 10.1111/0022-4146.00241
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Empirical Definitions of Spatial Labor Markets: The Roles of Competing Versus Complementary Growth

Abstract: ABSTRACT. If economic growth elsewhere raises an individual's earning prospects relative to his present location, then the individual will move. However, if the individual can exploit economic growth elsewhere by commuting, he will not need to move to gain from the expansion. County-level data from eight states in the Midwest over the period 1969-1994 are used to show that local county population responds positively to own-county economic growth, economic growth in the adjacent county, and economic growth two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 28 publications
(24 reference statements)
2
34
0
Order By: Relevance
“…Renkow (2003) found that a substantial portion (one-third to one-half) of new jobs is taken by incommuters. Khan, Orazem, and Otto (2001) found that economic growth in one community positively interacts with growth in nearby communities, possibly through commuting. Because we show that agglomeration increases new firm entry, we can conjecture that commuting is sensitive to agglomeration economies as well.…”
Section: Agglomeration Economies and Commuting Patternsmentioning
confidence: 98%
“…Renkow (2003) found that a substantial portion (one-third to one-half) of new jobs is taken by incommuters. Khan, Orazem, and Otto (2001) found that economic growth in one community positively interacts with growth in nearby communities, possibly through commuting. Because we show that agglomeration increases new firm entry, we can conjecture that commuting is sensitive to agglomeration economies as well.…”
Section: Agglomeration Economies and Commuting Patternsmentioning
confidence: 98%
“…In a core-periphery approach applied to urban and rural areas, the most remote regions may suffer from a lower intensity of linkages with urban regions, having in turn fewer chances to benefit from the development of the urban core (Vodden et al, 2010). Consistently with this hypothesis, Kahn et al (2001) -in an analysis at county level in the US -show that spread effects dominate until a certain distance, after which they become negative.…”
Section: Urbanmentioning
confidence: 64%
“…The higher the size of the regional economy, the higher its opportunity for growth, also in terms of population. Consistently with Kahn et al (2001), scale economies yield a comparative advantage in attracting migrants.…”
mentioning
confidence: 75%
“…Spatial externalities are believed to play a role in the new geographic economy (Fujita, Krugman, and Venables 1999). Indeed Khan, Orazem, and Otto (2001) found that wage growth in neighboring counties complemented population growth in the home county. However, agglomeration diseconomies arising from past manufacturing activity in urban areas (e.g., congestion, higher land values, pollution, higher labor costs) are one reason rural manufacturing was able to experience significant employment growth in the Midwest in the 1970s and 1980s (Haynes and Machunda 1987).…”
Section: Location Characteristicsmentioning
confidence: 99%